Beneath the Pretty Wrapping: Concealing and Revealing the Grim Reality of Incarceration - Aloisa, Pam; Newmiller, William (Academic Quarter | Akademisk kvarter, 2012)
Human rights issues are increasingly common subjects for artists, translated in a variety of media and hybrid forms. Art is action; activism and social research are two terms that define the po¬litical field that has gained prominent status in the contemporary art scene. Consideration of wrongful convictions in the United States is more than an academic inquiry. The article considers and analyses works of art created in the context of incarceration. Artists are William and Todd Newmiller and Pam Aloisa.